Vascular risk factors for COVID-19 ARDS: endothelium, contact-kinin system - Bailey, Melanie; Linden, Dermot; Guo-Parke, Hong; Earley, Olivia; Peto, Tunde; McAuley, Danny F.; Taggart, Clifford; Kidney, Joseph (Frontiers in Medicine, 2023)
SARS-CoV-2 binds to ACE2 receptors, expressed within the lungs. Risk factors for hospitalization include hypertension, diabetes, ischaemic heart disease and obesity–conditions linked by the presence of endothelial pathology. Viral infection in this setting causes increased conversion of circulating Factor XII to its active form (FXIIa). This is the first step in the contact-kinin pathway, leading to synchronous activation of the intrinsic coagulation cascade and the plasma Kallikrein-Kinin system, resulting in clotting and inflammatory lung disease. Temporal trends are evident from blood results of hospitalized patients. In the first week of symptoms the activated partial thromboplastin time (APTT) is prolonged. This can occur when clotting factors are consumed as part of the contact (intrinsic) pathway. Platelet counts initially fall, reflecting their consumption in coagulation. Lymphopenia occurs after approximately 1 week, reflecting the emergence of a lymphocytic pneumonitis [COVID-19 acute respiratory distress syndrome (ARDS)]. Intrinsic coagulation also induces the contact-kinin pathway of inflammation. A major product of this pathway, bradykinin causes oedema with ground glass opacities (GGO) on imaging in early COVID-19. Bradykinin also causes release of the pleiotrophic cytokine IL-6, which causes lymphocyte recruitment. Thromobosis and lymphocytic pneumonitis are hallmark features of COVID-19 ARDS. In this review we examine the literature with particular reference to the contact-kinin pathway. Measurements of platelets, lymphocytes and APTT should be undertaken in severe infections to stratify for risk of developing ARDS.